Intracholecystic papillary-tubular neoplasm. Issue 4 (April 2015) - Dekate, Jyoti; Serra, Stefano; Chetty, Runjan
Abstract Intracholecystic papillary-tubular neoplasm is a recently described terminology for the pre-invasive neoplastic mass forming lesions of the gallbladder. These lesions have recently gained importance due to their differing biological behaviour and clinical outcome from the flat type dysplasia of the gallbladder. In this paper, we would describe in detail about the defining criteria of Intracholecystic papillary-tubular neoplasm with emphasis on its pathological features, subtyping and clinical behaviour along with an exemplary case.